2017
DOI: 10.14238/pi57.2.2017.104-7
|View full text |Cite
|
Sign up to set email alerts
|

Duration and dose of antiepileptic drugs and serum calcium levels in children

Abstract: Background Many factors contribute to language development

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…Current study showed almost three fourth (74.1%) of children had global developmental delay followed by 5(18.5%) had speech delay, 1(3.7%) had motor delay and cognitive delay. In accordance with our study, authors reported that Global developmental delay (GDD) and intellectual disability (ID) affect up to 3% of the pediatric population [31,32]. The diagnosis of GDD is limited to children younger than 5 years old, but these children often evolve to meet diagnostic criteria for ID and probably represent the same population.…”
Section: Resultssupporting
confidence: 88%
“…Current study showed almost three fourth (74.1%) of children had global developmental delay followed by 5(18.5%) had speech delay, 1(3.7%) had motor delay and cognitive delay. In accordance with our study, authors reported that Global developmental delay (GDD) and intellectual disability (ID) affect up to 3% of the pediatric population [31,32]. The diagnosis of GDD is limited to children younger than 5 years old, but these children often evolve to meet diagnostic criteria for ID and probably represent the same population.…”
Section: Resultssupporting
confidence: 88%